2019
DOI: 10.1111/jfpp.14004
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, qualitative, and microbiological changes of minimally processed Brussels sprouts in response to coating with carboxymethyl cellulose/candelilla wax emulsion

Abstract: Minimally processed Brussels sprouts were coated which carboxymethyl cellulose/candelilla wax emulsion, packed in boxes with perforated wrap, and stored at 8°C. It was found that the emulsion not only was deposited on the surface but also penetrated into the inside of the heads through vascular system in stems and leaves. The coating did not affect weight loss, moisture content, and texture of the vegetables. In turn, reduced respiration rate, accelerated chlorophyll degradation, and increased activity of poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
(80 reference statements)
1
11
0
Order By: Relevance
“…Here, we observed that storage similarly increased the L values in leaves from both light treatments, indicating the lightening of them. Higher values in the L parameter have already been described for other green vegetables submitted to storage, such as green tomatoes, broccoli, rocket, Brussels sprouts, spinach, and lettuce [ 57 , 58 , 59 , 60 ]. Comparing the UV-B and control leaves, the treatment with radiation resulted in lower values of L , indicating a darker color of the UV-B leaves compared to the controls ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed that storage similarly increased the L values in leaves from both light treatments, indicating the lightening of them. Higher values in the L parameter have already been described for other green vegetables submitted to storage, such as green tomatoes, broccoli, rocket, Brussels sprouts, spinach, and lettuce [ 57 , 58 , 59 , 60 ]. Comparing the UV-B and control leaves, the treatment with radiation resulted in lower values of L , indicating a darker color of the UV-B leaves compared to the controls ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CMC can be versatile applied in various field such as drug delivery carrier [ 20 ], wound healing application [ 21 ], active corrosion protection [ 22 ], binder in ceramics [ 23 ], composited in hydrogel film [ 24 ] and hydrogel food packaging [ 25 ], fresh fruit and vegetable coatings [ 26 , 27 ] and hydrocolloid in noodles, bakery products and other foods [ 28 , 29 ] and it can produce composite films. CMC films exhibit many worthwhile attributes than many other biopolymers such as biodegradability, ease of production, forming a stable cross-linked matrix for packaging, etc.…”
Section: Introductionmentioning
confidence: 99%
“…As a recent trend, it must be remarked that natural coating materials are increasingly attracting the interest of researchers, as shown by the wide use of Aloe vera gel [138][139][140][141] and other natural polysaccharides, such as chitosan [9, 12, 25, 39, 74, 142, 147, 152, 164-166, 168-170, 172, 174, 179, 180, 186, 190, 193, 201], or seaweed extracts [148], which exhibit an intrinsic antimicrobial activity, significantly contributing to extending the product shelf life. The tendency toward natural products is also confirmed by the wide use of natural gums [47,181], starches [20, 188,195], cellulose, and its derivatives [32,167,173,175,194], and other compounds recovered from agri-food residues [144,183,203]. Glycerol is frequently used as a plasticizer, at concentrations ranging from less than 1 to 20%.…”
Section: Applications Of Edible Coatings To Food Productsmentioning
confidence: 95%